Productivity and economics of ber (Ziziphus mauritiana) based horti-pasture system as influenced by integrated nutrient management under rainfed condition of Rajasthan - MEENA, L R; KUMAR, DEVENDRA; MEENA, L K; SINGH, S P (The Indian Journal of Agricultural Sciences, 2019)
Awareness of food quality has shifted our focus on nutrient management system in crop production. Integrated nutrient management system resulted in good yield improvement and maintenance of soil health having least impact on food quality and environment. In order to assess the impact of different nutrient management systems, an experiment was conducted at ICAR-CSWRI, Avikanagar (Rajasthan) for two consecutive years during kharif 2012-13 and 2013-14 on sandy loam soil to ascertain the response of grasses and ber plants against integrated nutrient management system [no fertilizers, no organic manure (control), 100% RDF of NPK through sheep manure, 100% RDF of NPK through fertilizers and 50% RDF ( Recommended dose of fertilizers) of NPK through fertilizers+ 50% through sheep manure] under ber based hortipasture system. The results of study revealed that grass species had significant effect on yield and yield attributes. Yield and all the yield attributes were noticed higher in Cenchrus setigerus species than Cenchrus ciliaris except spike length. The highest green fodder (19.87 tonnes/ha), dry matter (4.48 tonnes/ha), grass seed (120.18 kg/ha) and protein content (7.36%) were found in Cenchrus setigerus species. While, ber (Ziziphus mauritiana) leaf (3.93 kg/plant), fruit ( 36.84 kg/plant) and fuel (23.31 kg/plant) were higher in association of Cenchrus setigerus than Cenchrus ciliaris. The maximum gross return of ` 104429/ha, net returns of ` 72029/ha and benefit: cost ratio (2.21) was registered in combination of Cenchrus setigerus and ber plants under horti-pasture system. In integrated nutrients management system, where 50% RDF of NPK through fertilizers +50% through sheep manure enhanced the growth and development of grasses as well as ber plants resulted significant increase in green fodder (80.71%), dry matter (35.07%), seed yield (36.14%), protein (26.62%), ber leaf (42.67%), fruit (47.34%) and fuel wood (90.31%) over control treatment. The maximum gross return (` 122374/ha) and net return (` 79652/ha) were realized where combined use of organic and inorganic sources of plant nutrients in grasses as well as in ber plants under ber based horti-pasture system. The higher benefit: cost ratio was also noticed with 100% RDF of NPK through fertilizers (2.19).